The Use of Canva and Powtoon Learning Media in Learning Poetry Materials to Improve Student Learning Outcomes for High School - Choirunnisa, Adinda; Yulandari, Esti; Tanjung, Muhammad Arif Alamsyah; Afifah, Riski Aprilia Nur; Kusnasari, Zanida (Lingua Franca, 2023)
This study aims to test the effectiveness of Canva and Powtoon learning media in learning poetry material to improve student learning outcomes in class X IPA 1 SMAN 1 Kelapa Kampit. The research subjects were class X IPA 1 students at Kelapa Kampit State Senior High School. The method used in this research is research and development. The application of information technology-based learning materials is expected to improve teaching standards in the classroom. The study results show that the Canva and Powtoon learning media are appropriate for learning Indonesian for class X IPA 1 SMA Negeri 1 Kelapa Kampit. This is because it meets the requirements for media validation, material validation, and evaluation validation. The pretest and posttest results found that Canva and Powtoon media helped class X IPA 1 SMA Negeri 1 Kelapa Kampit understand the material needed to recognize the atmosphere, themes, and meaning in the poetry anthology. Based on this, the Canva and Powtoon learning tools can be developed in teaching Indonesian, especially when teaching students how to recognize the atmosphere, themes, and meaning of poetry anthologies.